NOVEL STRATEGY FOR THE RAPID DETECTION AND CHARACTERIZATION FOOT-AND-MOUTH DISEASE VIRUS (FMDV) SEROTYPES O, A, AND ASIA 1 - W. Ali; M. Habib; R. S. A. Khan; S. Sajid; M. A. Zia; M. U. Mazhar; I. U. Khan; A. Javed; M. Farooq; M. S. U.; D. Shah (Journal of Animal and Plant Sciences, 2018)
A one-step RT-PCR assay was developed successfully for universal detection of Pakistani FMDV serotypes A, O and Aisa1 using newly designed universal primers MF5/MR3 that amplified complete VP1 coding gene and its PCR products can be used for direct sequencing. The assay amplified 995 bp region of the FMDV serotypes A, O and Asia1 directly from field samples including whole VP1 capsid protein-coding gene. Remarkably, PCR products acquired from this technique can be used in second PCR as DNA template for typing of serotypes O, A and Asai1 using serotype- specific primers. This second PCR enhanced the detection sensitivity of the assay evidently. In this study, this assay was used to identify and characterize FMDV isolates (n=34) collected from different outbreaks in Pakistan from 2014 to 2017. All the isolates (n=34) were successfully detected and categorized into serotype O (n=14), serotype A (n=5) and serotype Asia1 (n=15).This new assay will help in general detection in first PCR reaction (products of this PCR can be used for direct sequencing) while typing in second multiplex PCR. Therefore, amplified product can be used for detection, serotyping, sequencing, cloning, and other molecular studies of Pakistani, West Eurasian as well as universal FMDV’s strains. worldwide such as serotype O and A are distributed
Keywords: RT-PCR; serotyping; Pakistan; FMD.